DECISION SUPPORT SYSTEM DETERMINING RECIPIENTS OF THE PEOPLE'S HOUSING ASSISTANCE PROGRAM USING THE ELIMINATION AND CHOICE TRANSLATION REALITY METHOD (ELECTRE) - Herdian Mulyana, Iipandi; Gito Resmi, Mochzen; Ma’ruf Nugroho, Imam (RISTEC : Research in Information Systems and Technology, 2022)
In this era , the need for technology is indispensable in various fields of need, insepa rable from the economic field in the field of community welfa re, one of which is work programs to facilitate achieving goals, one of which is the work carried out by the Ministry of PUPR, namely the program for fla ts, specia l houses, and stimula nt assistance for self -help housing. based on pre-determined criteria. Electre is one of the methods used to rank and determine the best alternative. The basic concept of the electre method is to deal with outranking relationships by using pairwise comparisons between alternatives under each criterion separately. Which produces a computerized system that can automatically determine people who a re eligible to receive public housing assistance, based on the criteria va lues entered. This decision supportsystem is designed usingthe PHP programminglanguage.→Abstract